Flow behaviours comparison of crude oil–polymer emulsions. Issue 6 (18th August 2018) - Ghannam, Mamdouh; Abu-Jdayil, Basim; Esmail, Nabil
ABSTRACT: The flow characteristics of crude oil–polymer (COPE) emulsions were investigated in terms of viscosity and shear stress. Two commonly used polymers in the enhanced oil recovery were employed. These two different polymers are Alcoflood and Xanthan gum. Rheostress RS100 was used in this study for measuring and analysing the experimental measurements. A cone and plate sensor of RS100 rheometer was utilised for this investigation. The experimental measurements of viscosity and shear stress of different COPE were examined over the shear rate range of 0.1–1000 s −1 . The polymer concentration range of 500–10 4  ppm was examined and two crude oil concentrations of 25% and 75% by volume were tested. A detailed investigation of the flow behaviour of COPE in the presence of two different polymers was completed. The flow behaviour of all COPE exhibit non-Newtonian shear thinning behaviour that can be presented by the power-law model for crude oil-AF1235, however the other types of COPE can be predicted by the Casson model. For a low polymer concentration of 500 ppm, this investigation showed that the flow behaviour of Xanthan emulsions is slightly higher than the Alcoflood emulsions till a shear rate of 100 s −1 . For the higher polymer concentrations, both polymer emulsions exhibited more or less similar flow behaviours till the beginning of the shear thickening for the AF1285 emulsions.